2009
DOI: 10.1002/marc.200900335
|View full text |Cite
|
Sign up to set email alerts
|

SP–PLP–EPR Investigations into the Chain‐Length‐Dependent Termination of Methyl Methacrylate Bulk Polymerization

Abstract: Termination kinetics of methyl methacrylate (MMA) bulk polymerization has been studied via the single pulsed laser polymerization-electron paramagnetic resonance method. MMA-d(8) has been investigated to enhance the signal-to-noise quality of microsecond time-resolved measurement of radical concentration. Chain-length-dependent termination rate coefficients of radicals of identical size, k ti,i, are reported for 5-70 °C and up to i = 100. k ti,i decreases according to the power-law expression $k_{\rm t}^{i,i} … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
106
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(124 citation statements)
references
References 29 publications
18
106
0
Order By: Relevance
“…[29,30] Finally, there are the additional facts that measured values of k t 1,1 are in accord with small-molecule measurements [27] and are in broad quantitative agreement with Equation (2). [29] All these findings give confidence that k t 1,1 can now be accurately measured and that for many systems these values can largely be understood through the simple framework of the Smoluchowski and Stokes-Einstein equations.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…[29,30] Finally, there are the additional facts that measured values of k t 1,1 are in accord with small-molecule measurements [27] and are in broad quantitative agreement with Equation (2). [29] All these findings give confidence that k t 1,1 can now be accurately measured and that for many systems these values can largely be understood through the simple framework of the Smoluchowski and Stokes-Einstein equations.…”
Section: Introductionmentioning
confidence: 68%
“…[30,45] This suggests that any of the peculiarities of RAFT polymerization -such as cross-termination of the RAFT intermediate or variation of k t i,i with conversion -appear to have no significant effect on determination of k t i,i…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] Briefly, for MMA it has been found that α S • 0.65, [17][18][19] this parameter giving the variation of k t i,i with i for small ('S') chains. The crossover ('c') to long-chain behavior occurs at chain length i c • 100.…”
Section: Introductionmentioning
confidence: 99%